"If Carmen Can Analyze Shakespeare, Everybody Can": Positions, Conflicts, and Negotiations in the Narratives of Latina Pre-Service Teachers. Issue 2 (4th March 2018) - Kayi-Aydar, Hayriye
ABSTRACT: This study, focusing on the life stories of three pre-service Latina teachers in the United States, explored how they positioned themselves as learners of English and teachers of Spanish in their oral narratives, and how their past experience as minority students shaped their current professional identity negotiations as language teachers. Positioning analysis of their narrative accounts indicated that these female teachers, throughout their education, felt different or isolated because of their ethnic identity, language background, and socioeconomic class. They negotiated memberships in different communities across settings in their lives. Understanding the conflicts and struggles that they experienced and unique strategies that they used to overcome them will hopefully provide insights for all teachers and teacher educators in linguistically and culturally diverse contexts.